Effects of Ga deposition rate and Sb flux on morphology of GaSb quantum dots formed on GaAs. Issue 1 (7th September 2016) - Kawazu, Takuya; Noda, Takeshi; Sakuma, Yoshiki; Sakaki, Hiroyuki
Abstract : We investigate the effects of Ga deposition rate ( R Ga ) and Sb flux ( P Sb ) on the morphology of GaSb quantum dots (QDs). GaSb QDs are formed on GaAs at 420 °C by Stranski‐Krastanov (SK) mode under various conditions of R Ga (0.13‐0.73 monolayer (ML)/s) and P Sb (1.0‐4.2 × 10 ‐7 Torr). An atomic microscope study shows that the density n QD of GaSb QDs is markedly affected by P Sb and R Ga ; no (or few) QDs are formed at high R Ga (∼ 0.73 ML/s) and at low P Sb (≤1.2 × 10 ‐7 Torr). As R Ga ( P Sb ) increases, n QD first increases and then decreases. n QD reaches its maximum (∼1 × 10 11 cm ‐2 ), when the V‐III ratio is about 3.6. We also analyze the experimental data by using a rate equation model and discuss the dependences of n QD on R Ga and P Sb .